Regulatory push-pull effects on innovation: an evaluation of the effects of the REACH regulation on patents in the chemical sector - Claudia Ghisetti; Francesco Quatraro (WWWforEurope, 2015)
The Europe 2020 Strategy has identified the key goal of smart, more inclusive and sustainable growth. In this direction, redirecting firms' innovation activities towards ecological targets without hampering their competitiveness is of paramount importance. The double externality issue related to environmental innovations makes the policy intervention crucial in order to avoid sub-optimal commitment of resources to the innovation process and ensure the reduction of polluting agents emissions However, the positive outcome of any policy inducement mechanisms is not guaranteed, as different policy frameworks may generate different innovative outcomes. An in depth analysis of environmental policy instruments is therefore all the more necessary in order to gain knowledge on the state of the art and evaluate the scenarios for further improvements. In this perspective, the proposed research project will focus on two main research questions: 1. What are the main existing EU policy instruments explicitly designed to trigger environmental innovations? Which are their main features? 2. Which are the possible avenues leading to successful policy design? The first research question will be tackled by performing a desk research aiming at analyzing the main environmental regulations introduced in Europe so as to produce a clear and comprehensive taxonomy to shed light on common dimensions and main differences. The second research question will be addressed by carrying out empirical analyses based on simulation and econometric techniques. We will focus on a specific environmental policy in the chemical domain so as to draw useful insights on the effect of the policy aiming at redirecting innovation activities to environmental targets and also to highlight the main policy best practices.
Keywords: O33; Q53; Q55; Q56; R11; 330; Academic research; Industrial policy; Innovation; Innovation policy; Patents